Pengembangan Aplikasi Penggajian Karyawan Dengan Menggunakan Metode Agile Berbasis Mobile Android - Alda, Muhamad (Komputika : Jurnal Sistem Komputer, 2023)
The development of information technology is increasing, greatly affecting the human mindset in the process of meeting information needs and helping to complete work. Information technology is a tool or media that can help human life. PT. Sop Sumsum Langsa is a company engaged in the culinary field. In processing employee payroll data, PT. Sop Sumsum Langsa still uses a computer with a Microsoft Excel application. In this way, there are still obstacles and problems that occur. The author researches to help provide solutions in solving these problems by building an Android-based mobile application that can be used in the processing of employee salaries. The application development method used by the author is the agile method consisting of stages of system analysis, design, application development, testing, application deployment, revision and evaluation, and system maintenance. In testing the application, the author uses the black box testing method. The results of the research conducted by the author are an android-based mobile application that can help PT. Sop Sumsum Langsa in processing employee salary data effectively and efficiently.